Extraction of cellulose and microcrystalline cellulose from kenaf - Yoong, Li Hua; Shuhaida Harun,; Mohd Shaiful Sajab,; Jamaliah Md Jahim,; Siti Syazwani Mohd Shah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Bast and core of kenaf which categorized as agriculture residues were used in the extraction of cellulose due to its lignocellulosic nature. In this study, cellulose was extracted from the raw kenaf by using 10% alkaline peroxide pre-treatment followed by extraction process at 85 °C using the combination of 20% (v/v) formic acid and 10% (v/v) hydrogen peroxide that formed peroxy acid. The extracted cellulose was further hydrolyzed by 1.5 M of hydrochloric acid at 80 °C to yield microcrystalline cellulose (MCC). Relatively high yield of 71.81% (w/w) and 94.8% (w/w) were achieved for extracted cellulose and MCC, respectively. Based on FESEM, the average diameter of kenaf cellulose and MCC were 12.43 μm and 11.64 μm, respectively with the separated fibrils and rod-like structural. FT-IR spectral peaks observed in the cellulose and MCC revealed that most hemicellulose and lignin were eliminated during the chemical treatments. XRD analysis results exhibited that kenaf MCC gives the sharpest and highest peak s compared to others. The results also showed that the crystallinity index of extracted cellulose and MCC were increased to 60.5% and 62.3%, respectively.